Jenis Ikan di Kawasan Konservasi (Lubuk Larangan) Sungai Bangko, Kabupaten Solok Selatan, Provinsi Sumatera Barat, Indonesia - Azrita, Azrita; Syandri, Hafrijal; Bukhari, Bukhari; Asmaida, Asmaida (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
The conservation Area (lubuk larangan) is one of the fish resource conservation areas. However, recently, the types of fish that live in this area have become increasingly threatened due to environmental changes and non-selective fishing. Therefore, it is important to study the diversity of freshwater fish in the conservation area (Lubuk Larangan) located along the Bangko River, Luak Kapau Village, South Solok Regency, West Sumatra Province, Indonesia. This data will be valuable in determining which fish species should be prioritized for domestication as potential candidates for fish cultivation. The process of collecting fish is carried out between June and July 2020 by involving the assistance of local fishermen who use various types of fishing gear, including gill nets, spread nets, trap nets, and fishing rods. The findings from this study revealed the existence of 13 fish species belonging to three orders, six families, and thirteen genera. Among the species collected, the family Cyprinidae was the most dominant, accounting for 61.53% of the total fish population collected, followed by the families Cobitidae, Bangridae, Cichlidae, Mastacembelidae, and Gobiidae, each consisting of 7.69%. of the total. The species Acanopsis octoactinotus was identified as vulnerable, while Sicyopterus aeinsis was classified as near threatened. The level of functioning of the conservation area for fish preservation is 84.35%, which is included in the very well functioning category. Priority should be given to breeding programs and restoration initiatives targeting future populations of endangered freshwater fish.